2022
DOI: 10.1111/acps.13397
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions to diminish cognitive side effects of electroconvulsive therapy: A systematic review and meta‐analysis

Abstract: Objective The authors conducted a systematic review and meta‐analysis of pharmacological interventions to diminish cognitive side effects of ECT. Methods Electronic databases of Pubmed, PsycInfo, Embase and Scopus were searched from inception through 1 April, 2021, using terms for ECT (e.g. electroconvulsive therapy), cognitive outcome (e.g. cogni*) and pharmacological intervention (e.g. calcium channel blocker and general terms, like protein). Original studies with humans receiving ECT were included, which ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Similarly, donepezil was not found to improve cognitive performance in an RCT that compared donepezil to placebo 38 , 39 . However, a recent meta-analysis found statistically significant improvement in cognitive function with memantine and liothyronine with moderate to large effect sizes, but the quality of the evidence was generally poor due to insufficient number of studies, small sample size, differences in study methodology and risk of bias 40 . The negative outcomes of these studies may be because a different mechanism, not addressed by these drugs, may underlie the cognitive impairment associated with ECT.…”
Section: Ect Augmentationmentioning
confidence: 99%
“…Similarly, donepezil was not found to improve cognitive performance in an RCT that compared donepezil to placebo 38 , 39 . However, a recent meta-analysis found statistically significant improvement in cognitive function with memantine and liothyronine with moderate to large effect sizes, but the quality of the evidence was generally poor due to insufficient number of studies, small sample size, differences in study methodology and risk of bias 40 . The negative outcomes of these studies may be because a different mechanism, not addressed by these drugs, may underlie the cognitive impairment associated with ECT.…”
Section: Ect Augmentationmentioning
confidence: 99%
“…Other studies have found functional brain connectivity (fMRI) changes in the salience-, frontoparietal-, and default mode-networks which correlated with cognitive changes ( 9 ). Regarding preventive strategies to diminish cognitive side-effects, a comprehensive meta-analysis has found evidence for protective effects of liothyronine and memantine in ECT, underlining the divergent hypotheses regarding the pathophysiological mechanisms causing postictal confusion and cognitive deterioration after ECT ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate or alleviate CSEs, extensive research has been dedicated to pharmacological interventions [15]. Notably, although promising medications like liothyronine [16], memantine [17,18], and galantamine [19] have been reported to potentially alleviate CSEs, further rigorous trials are indispensable to verify their appropriateness for routine clinical application.…”
mentioning
confidence: 99%